The Effect of Internal Service Quality and Workload on Job Satisfaction at Royal Prima General Hospital - Anita Sari, Devi; Novalinda Ginting, Chrismis; Nasution, Sri Wahyuni (The Islamic Education and Multiculturalism Foundation, 2025)
Job satisfaction is the difference between expectations and reality of the benefits obtained at work. In general, job satisfaction reflects a person's attitude towards their work. Qualified human resources who have good performance are difficult to obtain, because job satisfaction is influenced by various factors, such as Internal Service Quality and workload. This study aims to analyze the effect of Internal Service Quality and workload on job satisfaction at RSU Royal Prima Medan. This research is a descriptive quantitative study with a cross-sectional design. The study population involved 623 employees of RSU Royal Prima Medan, both medical and nonmedical. The sample was taken using systematic sampling method, with a minimum number of 185 respondents based on the calculation of 5 times the number of indicators (37 indicators). Data collection was conducted through questionnaires, and data analysis included univariate, bivariate, and multivariate analysis. The results showed that the majority of respondents were 31-40 years old (49.2%), female (78.4%), had the latest education S1 (53.5%), and had a length of work of more than 2 years (82.7%). Bivariate analysis shows that Internal Service Quality has a significant influence on job satisfaction with a p-value of 0.000 (<0.05). Similarly, workload significantly influenced job satisfaction with a p-value of 0.000 (<0.05). Multivariate analysis shows that the Internal Service Quality factor is the most dominant variable affecting job satisfaction at RSU Royal Prima Medan. Internal service quality and managing workload to improve employee job satisfaction.